Da'wah Regarding Human Rights in the Implementation of Workers' Rights in Islam: A Study of Hadith Bukhari number 1930 from the Muhaddist's View - Noor Hamid; Damanhuri (al-Afkar, Journal For Islamic Studies, 2024)
The Qur’an and Al-Hadith are the sources of the concept of Islamic work ethics. Islam teaches that hard work can be forgiven for sins and there is nothing better than eating the fruits of one's work. Hadith Bukhari Number 1930 states that: "No one eats any food that is better than food produced by his own hands". To protect the human rights of workers, Islam pays great attention to their rights because in essence workers facilitate work. These rights including being treated with respect and dignity, being informed about their wages, getting work that suits their skills, getting paid promptly, and taking care of their health. This paper concludes that human rights values are embedded in Islamic teachings, this is proven by their presence basic principles of human rights and values in the Al-Qur'an and Hadith, as well as in the practice of Islamic life. Upholding the principles of human rights is in line with Islamic teachings and can bring benefits and peace to the planet, so that That humans can live well and happily is a worship that should be grateful for